Caracterização citogenética clássica e molecular de trigos brasileiros - Urio, Elisandra Andreia (2013)
The present study sought to characterize cytogenetically and infer the genetic stability of Brazilian wheat cultivars. The biological material consisted of old and modern cultivars, all kept in the Active Germplasm Bank of Embrapa Wheat, consisting of two distinct groups. In group 1, it was selected 17 cultivars launched after the year 2000, which were evaluated for the presence of micronuclei in tetrads, and the pollen viability. In group 2, it was selected 70 cultivars launched before the year 2000, which were evaluated for pollen viability,. For tetrad analysis, they were classified as normal (absence of micronuclei), triads and micronuclei. To check pollen viability, pollen grains it was classified as viable (two and three nuclei and the presence of starch) and nonviable (empty), by the size and presence of more than one pore. Specifically for group 1, cultivars BR 24, Timbaúva BRS, BRS 208 and BRS 220 were selected by greater variability estimated, determined by Tocher method, aiming the chromosomal characterization through In Situ Hybridization (FISH and GISH). For FISH, probles were used as synthetic oligonucleotides (AAC) 5 and (AAG) 5, present in the three wheat genomes. For GISH, the genomic DNA of rye was used as probe to verify the translocation 1BL.1RS. Data were analyzed by Scott-Knott 5% test. For group 1, the analysis of tetrads found a significant difference in the presence of micronuclei and on the pollen viability, only on the variable size difference. In group 2, it was found nonviable, viable and size difference pollen grains. For FISH analysis, all cultivars showed distinct marking sites for both (AAC) 5 and for (AAG) 5. However, the oligonucleotide (AAC) 5 was more strongly marked in all materials, demonstrating variability among cultivars. For GISH, BRS 208 was the only one that presented the translocation 1BL.1RS. Therefore, the results generated can serve as support in genetic improvement projects, particularly in the incorporation of desirable agronomic characteristics present in the cultivars analyzed, as well as to produce hybrids between T.aestivum and different Triticeae species